Chilton 2006 European Mechanical Service Manual - Chilton (Cengage Learning, Inc, 2006)
The Chilton 2006 European Mechanical Service Manuals provides updated coverage through 2005 models and even many 2006 models, as made available from original equipment manufacturers (OEMs). Chilton is still your reliable source for fast, accurate repairs and reassembly and it still provides the lowest-priced professional repair manuals on the market! This manual is organized by make, model and system so information gathering is easier. Now with even more illustrations and a streamlined index, it's no wonder more automotive professionals turn to Chilton Professional Manuals for their mechanical service and repair information